Phytolith production-weighed meteorological averages from West Africa (Benin and Senegal) - Anne Alexandre (PANGAEA, 2025)
Daily and daytime meteorological averages calculated for the sampled years and rainy seasons at Belefoungou (BE, Benin, Nalohou (NA, Benin) and Dahra (DA, Senegal) from 2018 to 2021.
In: Alexandre, A (2025): Climate and triple oxygen isotope of precipitation, groundwater, soil water, plant water, and phytolith data from West Africa (Benin and Senegal) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984133